1961
DOI: 10.1246/bcsj.34.952
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Various Elements between Nitric Acid and Anion Exchange Resin

Abstract: Distribution coefficient of some metallic elements between nitric acid and anion exchange resin were measured. From the results described above, the fundamental data on the separation of each element in nitric acid were obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1964
1964
2006
2006

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…As can be seen in Fig. 2, the SiPyR-N4 resin exhibits a quite strong adsorption to some rare earths especially the light rare earth elements such as La(III), Ce(III), Pr(III), Nd(III) and Pm(III) with which the distribution coefficients reach 10-25 dm 3 /kg-resin, which is several times higher than that of heavy rare earth elements and much higher than the values reported for these elements with conventional anion exchange resins [4,5]. In addition, it is also found that the adsorption of these elements is promoted by the increasing nitric acid concentration up to ca.…”
Section: Column Separation Experimentsmentioning
confidence: 72%
See 1 more Smart Citation
“…As can be seen in Fig. 2, the SiPyR-N4 resin exhibits a quite strong adsorption to some rare earths especially the light rare earth elements such as La(III), Ce(III), Pr(III), Nd(III) and Pm(III) with which the distribution coefficients reach 10-25 dm 3 /kg-resin, which is several times higher than that of heavy rare earth elements and much higher than the values reported for these elements with conventional anion exchange resins [4,5]. In addition, it is also found that the adsorption of these elements is promoted by the increasing nitric acid concentration up to ca.…”
Section: Column Separation Experimentsmentioning
confidence: 72%
“…Although an ion exchange process has many advantages such as organic solvent free and little waste generation, compacted equipment, simple operation procedure and economical improvement [1][2][3], ion exchange technology has not been applied for industrial use as a main rare earths separation process due to its slow adsorption and elution kinetics for conventional anion exchange resins with quaternary ammonium as functional group [4,5], and to the instability of organic resin in a strong acid medium. Generally, anion exchange resins are polymer-based matrix with which a column separation is affected by the swelling and the pressure drop associated with liquids change.…”
Section: Introductionmentioning
confidence: 99%
“…8 Distribution coefficients, Kd, for Th have been determined at different concentrations of nitric acid under static and dynamic conditions. 14,15 A systematic survey of the anion exchange behavior of various elements in nitric acid solutions has been carried out by ICH1KAWA et al 16 From these relevant data, it can be seen that the adsorption of Th on the resin was the highest in the region from 7 to 8M HNO 3. At that acid concentration, the K d values for Th were found to be about 200-300.…”
Section: Resultsmentioning
confidence: 99%
“…Because the adsorption of uranium on an anion-exchange resin in pure aqueous nitric acid (e.g. 8 mol dm -3 ) is very weak, 17 the medium is not applicable for the simultaneous separation of uranium and thorium. On the other hand, a magnesium nitrate medium allows uranium and thorium to be adsorbed to a great extent with high salting-out strength.…”
Section: Analysis Of Uranium-thorium Ore Mock Solutionmentioning
confidence: 99%